The ambiguities of desistance: ex-offenders, higher education and the desistance journey - Honeywell, David (Emerald points, 2021)
Introducing nuanced and rich data around the growing interest in desistance and what leads someone to move away from crime, this book explores the ongoing and individual desistance journeys of ex-offenders during re-integration into society. Through in-depth interviews and his own lived experiences as a prisoner, the author highlights the importance of Higher Education in the desistance process as a conduit for change and rehabilitation. He explores the complex life process of the ex-offender, investigating the introspective and existential experiences that lead individuals towards an ongoing desistance journey in which they re-evaluate their sense of selves and develop new identities. Arguing that in the current criminal justice system the focus on crime overshadows the more complex and unending process of desistance, the author showcases how the system provides no formal rite of passage for ex-offenders attempting to re-integrate into society. In response to this, this book synthesises and critically reviews desistance theory as it has emerged within contemporary criminology, and offers an opportunity for readers to engage with the complexities of the lives analysed in this research.